MODERN MODELS OF PEDAGOGICAL EDUCATION AND PROFESSIONAL TRAINING - Aydarov Erkin Bakitovich (Web of Journals Publishing, 2024)
The article analyzes current trends in the training of pedagogical specialists. Innovative technologies used in teacher education and the importance of their use are also explored.
Keywords: education, teacher education, teacher, concept of lifelong education, model of teacher training, model of continuous professional development.